Implementasi Zakat dan Penghapusan Riba dalam Pemikiran Muhammad Nejatullah Siddiqi - Hidayatul Murteza, Yusfa; Abdul Aziz, Jamal (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This literature research examines the implementation of zakat and the elimination of usury in the thoughts of Muhammad Nejatullah Siddiqi with the aim of analyzing this figure's thoughts. This research is a type of descriptive qualitative research. The results of the study show that Muhammad Nejatullah Siddiqi, as a contemporary mainstream Islamic economic figure, prioritizes the implementation of zakat and the elimination of usury as the main characteristics of an Islamic-based economy. Zakat is seen as mandatory for the rich, a right for the less fortunate, and the state plays a major role in managing it. Muhammad Nejatullah Siddiqi emphasized that zakat is not just a charity or tax, but involves almost all types of assets with predetermined collection rates. Siddiqi's view emphasizes the need to eliminate usury in accordance with the prohibitions of the Koran, especially in the practice of compounding loan debts. Muhammad Nejatullah Siddiqi's criticism of Islamic banks emphasizes the increase in mudharabah activities rather than murabahah practices